Pengembangan LMS Moodle Berbasis PBL Untuk Mengukur Keefektifan Hasil Belajar Kognitif pada Elemen Analisis Data di Smk Sejahtera Surabaya - Eka Yunizar Zaimatus Sa'diyah; Rindu Puspita Wibawa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This research is motivated by the cognitive stagnation of vocational school students in the Data Analysis element, which is mostly limited to lower-order thinking skills (LOTS) and has not met the analytical problem-solving target (C4). This is caused by abstract materials and the use of fragmented digital tools that trigger cognitive overload. As a solution, this study aims to develop and measure the effectiveness of a Moodle Learning Management System (LMS) integrated with Problem Based Learning (PBL) syntax. The method used is Research and Development (R&D) with the ADDIE approach (Analyze, Design, Development, Implementation, Evaluation). The field testing applied a Quasi-Experimental Non-Equivalent Control Group Design involving an experimental class and a control class at SMK Sejahtera Surabaya. The results showed that the product feasibility achieved a "Highly Valid" predicate with validation scores from the learning design (RPM) expert at 92%, media expert at 90%, material expert at 90%, and evaluation instruments at 89.29% (average 90.32%). Practicality evaluation using the User Experience Questionnaire (UEQ) obtained positive responses in the Good and Above Average categories. Effectiveness testing proved that the experimental class using the PBL-based Moodle LMS experienced a significant improvement in cognitive learning outcomes (C1-C4) with an average N-Gain score of 0.44 (Moderate), in contrast to the control class which only obtained a score of 0.21 (Low). In conclusion, the PBL-integrated Moodle LMS is proven to be valid, practical, and highly effective in improving students' analytical cognitive abilities.